VEINS AND HYDROTHERMAL BRECCIAS OF THE RANDU KUNING PORPHYRY Cu-Au AND EPITHERMAL Au DEPOSITS AT SELOGIRI AREA, CENTRAL JAVA INDONESIA - Sutarto Sutarto; Arifudin Idrus; Agung Harijoko; Lucas Donny Setijadji; Franz Michael Meyer (Geological Engineering Department Universitas Gadjah Mada, 2015)
The Randu Kuning prospect is situated at Selogiri area, Wonogiri, Central Java, Indonesia. This location is about 40 km to the south-east from Solo city or approximately 70 km east of Yogyakarta city. Many Tertiary dioritic rocks related alterationmineralisation were found at the Randu Kuning area and its vicinity, including hornblende microdiorite, hornblende-pyroxene diorite and quartz diorite. Mineralisation type of the Randu Kuning prospect was interpreted as porphyry Cu-Au and a number epithermal Au-base metals deposits in its surrounding. The closed existing of porphyry Cu-Au and epithermal Au-base metals type deposits at the Randu Kuning area produced a very complex of veins and hydrothermal breccias crosscutting relationship. A lot of porphyry veins types were found and observed at the Randu Kuning area, and classiﬁed into at least seven types. Most of the porphyry veins were cross cut by epithermal type veins. Many epithermal veins also are found and crosscut into deeply porphyry vein types. There are genetically at least two type of hydrothermal breccias have recognized in the research area, i.e. magmatic-hydrothermal breccia and phreatomagmatic breccia. Magmatic hydrothermal breccias are mostly occured in contact between hornblende microdiorite or quartz diorite and hornblende-pyroxene diorite, characterized by angular fragments/clasts supported or inﬁlled by silicas, carbonates and sulphides matrix derived from hydrothermal ﬂuids precipitation. Phreatomagmatic breccias are characterized by abundant of the juvenile clasts, indicated contact between hot magma with ﬂuid or water as well as many wall rock fragments such as altered diorites and volcaniclastic rock clasts set in clastical matrix. The juvenile clasts usually compossed by volcanic glasses and aphanitic rocks in rounded-irregular shape. Both veining and brecciation processes have an important role in gold and copper mineralisation of the Randu Kuning Porphyry Cu-Au and epithermal Au-base metals deposits, mostly related to the presence of quartz veins/veinlets containing signiﬁcant sulphides, i.e., quartz with thin centre line sulphides (Abtype) veins, pyrite±chalcopyrite (C type) veinlets, pyrite+quartz± chalcopyrire±carbonate (D type) veins of porphyry types as well as epithermal environment quarts+ sulphides+carbonate veins.